The Costs of Legitimacy for Political Institutions. Issue 1 (9th February 2022) - Agné, Hans; Söderbaum, Fredrik
Abstract: Can political institutions be too legitimate for their own good? The standard view of legitimacy treats it purely as a resource—political institutions that enjoy legitimacy can draw on voluntary cooperation among their subjects to reach their aims, which is believed to make them more effective than institutions that lack legitimacy and must instead use coercion or bribery to reach aims. We challenge this conventional wisdom by advancing a more general theory that is sensitive also to the costs of legitimacy. High levels of legitimacy, we suggest, can make political actors complacent about the status quo and cause them to pay insufficient attention to problems related to implementation. In contrast, low levels of legitimacy—or legitimacy crises—can serve as a wake-up call and motivate actors to work harder to reach their original or wider goals. We illustrate this theory through a case study of the African Union, assessing when and how legitimacy serves as a cost or as a resource for political institutions, with implications for decision-making, implementation, and effectiveness.